RTS,S/AS01E Malaria Vaccine Induces Memory and Polyfunctional T Cell Responses in a Pediatric African Phase III Trial - Moncunill, Gemma; De Rosa, Stephen C.; Ayestaran, Aintzane; Nhabomba, Augusto J.; Mpina, Maximillian; Cohen, Kristen W.; Jairoce, Chenjerai; Rutishauser, Tobias; Campo, Joseph J.; Harezlak, Jaroslaw; Sanz, Héctor; Díez-Padrisa, Núria; et al. (Frontiers in Immunology, 2017)
Comprehensive assessment of cellular responses to the RTS,S/AS01E vaccine is needed to understand potential correlates and ultimately mechanisms of protection against malaria disease. Cellular responses recognizing the RTS,S/AS01E-containing circumsporozoite protein (CSP) and Hepatitis B surface antigen (HBsAg) were assessed before and one month after primary vaccination by intracellular cytokine staining and 16-color flow cytometry in 105 RTS,S/AS01-vaccinated and 74 rabies-vaccinated participants (controls) in a pediatric phase III trial in Africa. RTS,S/AS01E-vaccinated children had significantly higher frequencies of CSP- and HBsAg-specific CD4+ T cells producing IL-2, TNF-α and CD40L and HBsAg-specific CD4+ T producing IFN-γ and IL-17 than baseline and the control group frequencies. Vaccine-induced responses were identified in both central and effector memory compartments. Effector memory CD4+ T cells expressing IL-4 and IL-21 were detected recognizing both vaccine antigens. Consistently higher response rates to both antigens in RTS,S/AS01E-vaccinated than comparator-vaccinated children were observed. RTS,S/AS01E induced polyfunctional CSP- and HBsAg-specific CD4+ T cells, with a greater degree of polyfunctionality in HBsAg responses. In conclusion, RTS,S/AS01E vaccine induces T cells of higher quality and complexityfunctional heterogeneity and polyfunctionality than previously characterized. Responses detected in memory CD4+ T cell compartments may provide correlates of RTS,S/AS01-induced immunity and duration of protection in future correlates of immunity studies.